A review on diffusion modelling in hydrogen related failures of metals. (August 2016) - Díaz, A.; Alegre, J.M.; Cuesta, I.I.
Abstract: Modelling of hydrogen embrittlement in order to prevent engineering failures requires a characterization of transport phenomena in the bulk metallic as a first step. Interstitial solid state diffusion can be described as a random phenomenon, however there will be also some drift forces biasing this behaviour so a modification in Fick's laws is needed. The potential energy landscape of the metal lattice characterizes the influence of imposed fields and microstructural defects in transport kinetics. Thus, considering the chemical potential as a driving force, the physical basis of diffusion will be translated into continuum equations. Finally the two-level models that take into account lattice and trapping sites for hydrogen will be reviewed. Graphical abstract: Highlights: Hydrogen related failures. Fracture and crack propagation in metals is drastically affected by the presence of hydrogen. Multiscale modeling and simulation . Crack tip modelling when hydrogen is involved requires a multiscale approach. Diffusion and Interstitial solid state solutions. Random motion and chemical potential gradients drive diffusion. Hydrogen trapping and stress-strain state. Trapping and the influence of stress-strain state are discussed.